The Impact of Green Training on Environmental Performance: The Mediating Role of Employee Performance - Sajjad Ahmed,; Sikandar Ali Malookhani,; Prof. Dr. Seema N. Mumtaz,; Naveed Ali Qureshi,; Dr. Qasim Mansoor Jalali, (Dialogue Social Science Review (DSSR), 2025)
Companies are encouraged to adopt greener practices to reduce their environmental impact. However, this study examines the role of green training in enhancing environmental performance and its indirect impact on employee performance (EP). As corporations face mounting pressure to implement environmentally responsible practices, this research provides empirical evidence on how strategic human resource investments can promote sustainable outcomes. The study employs a robust methodological approach, collecting primary data from 314 employees across various manufacturing sectors through a structured questionnaire that utilizes validated 5-point Likert scales (GT α = 0.89, EP α = 0.94, ENP α = 0.91). The findings indicate that green training enhances environmental performance. Furthermore, employee performance was found to partially mediate this relationship, implying that green training boosts employee skills and environmental awareness, which in turn improve organizational environmental results. The findings offer empirical support for green training and environmental performance strategies. This study advances the green HRM literature and provides policymakers and HR practitioners with practical guidance on promoting sustainability through employee development.